Rasch-Based DIF Analysis of Self-Harm Behaviors: Gender, Ethnicity, and Age Factors in an Indonesian Context - Yuda Syahputra; Ifdil Ifdil; Caroline Lisa Setiawati; Frischa Meivilona Yendi; Yuliana Yuliana; Romi Fajar Tanjung; Susiati Susiati (Asosiasi Asesmen Pendidikan (AAP), 2026)
This study was conducted because self-harm behavior in adolescents has become a serious problem that requires in-depth attention, especially in Indonesia, where this phenomenon continues to increase. Factors such as gender, ethnicity, and age are believed to play an important role in influencing self-harm behavior, but comprehensive empirical studies on the interaction of these three factors are still limited. The objectives of this study were to identify differences in self-harm behavior based on gender, ethnicity, age, and investigate the interaction between these three factors. The research method used a quantitative design with a survey approach. The sample consisted of 812 adolescents who were randomly selected from various regions in Indonesia, and data were collected through questionnaires measuring the level of self-harm behavior and demographic factors. Data were analyzed using ANOVA in the Rasch model. The results showed that females have higher rates of self-harm than males. Bugis (B) and Flores (F) cultures show higher self-harm scores compared to other age groups. In addition, the 15-17 age group shows higher self-harm scores compared to other age groups. The conclusion of this study is that there are significant differences in self-harm behavior in adolescents based on gender, ethnicity, and age